Titanium alloy with ultrafine grain structure and preparation method thereof

Through ball mill-discharged plasma sintering-quenching-discharge and plasma heat deformation method, prepare titanium alloy materials with ultra-fine crystal tissue, solve the problem of insufficient strength and stability of the material in the traditional titanium alloy preparation method, and realize high intensity And toughness, and improve the heat and mechanical stability.

CN116060623BActive Publication Date: 2025-01-24BEIJING INST OF TECH TANGSHAN RES INST +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211565900.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-07
Publication Date
2025-01-24
Estimated Expiration
2042-12-07

AI Technical Summary

Technical Problem

It is difficult to obtain high-strength and tough materials with ultrafine microstructures in traditional titanium alloy preparation methods, and the prior art has limitations in thermal instability and mechanical instability.

Method used

Titanium alloy materials are prepared using the method of ball milling-discharge plasma sintering-quenching-discharge plasma thermal deformation. The powder is uniformly mixed through ball milling, SPS sintering to obtain an equiaxed structure, quenching to form a needle-like structure, and then discharge plasma thermal deformation to obtain an ultra-fine grained structure. .

Benefits of technology

It achieves the high strength and toughness of titanium alloy materials, improves the thermal and mechanical stability of the material, and overcomes the problems of grain coarsening and uneven structure in traditional methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116060623B_ABST
    Figure CN116060623B_ABST
Patent Text Reader

Abstract

The present invention relates to a titanium alloy with ultrafine grain structure and a preparation method thereof, and belongs to the technical field of metal material preparation. The method is as follows: titanium alloy powder and copper powder are added into a ball mill, ball milled and mixed, evaporated and dried to obtain a uniform mixed powder; then the mixed powder is loaded into a graphite mold, and spark plasma sintering is performed in an SPS system; then the sample prepared by SPS sintering is quenched; finally, the quenched sample is subjected to SPS thermal deformation. The method adopts "mechanical ball milling-spark plasma sintering-quenching-spark plasma thermal deformation" to prepare a titanium alloy material with ultrafine grain structure. The method is simple and easy to operate, has low energy consumption, can obtain a titanium alloy material with ultrafine grain structure with high strength and good toughness, and has good market application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a titanium alloy with ultrafine grain structure and a preparation method thereof. The method combines ball milling-discharge plasma sintering-quenching-discharge plasma thermal deformation and belongs to the technical field of metal material preparation. Background Art

[0002] Titanium alloy is one of the most noteworthy metal materials in the 21st century. It has the advantages of high specific strength, low density, excellent wear resistance and good biocompatibility. It has broad application prospects in aerospace, military technology, civilian automobiles, aircraft carriers and ships, and biomedicine.

[0003] It is well known that grain refinement can significantly improve the mechanical properties of materials, such as strength, toughness, corrosion resistance, and processing performance. However, in the preparation process of titanium alloys prepared by traditional ingot casting, the large volume fraction of grain boundaries and the high preparation temperature provide a strong driving force for grain coarsening. Therefore, it is still a challenge to construct high-strength and toughness titanium alloys with ultrafine microstructures. At present, the methods for obtaining ultrafine titanium alloy structures include equal-diameter angular channel extrusion technology and high-pressure torsion deformation technology. However, the thermal instability and mechanical instability of ultrafine-grained titanium alloy structures prepared by these technologies severely limit their application in engineering practice.

[0004] Spark plasma sintering (SPS) is a new powder sintering technology developed in recent years. It combines the temperature field excited by the electric field with the external force field to achieve rapid densification of materials. At present, SPS has been widely used in the preparation of metal materials, ceramic materials and composite materials. Although SPS technology can quickly densify titanium alloy materials and obtain fine grains, the thermal inhomogeneity generated during the heating process makes the prepared titanium alloy structure present a significant gradient distribution.

[0005] Therefore, it is of great significance to explore a simple and efficient preparation method to prepare titanium alloy materials with ultrafine grains and excellent mechanical properties. Summary of the invention

[0006] In view of this, the object of the present invention is to provide a titanium alloy with an ultrafine grain structure and a preparation method thereof. The method adopts "ball milling-spark plasma sintering-quenching-spark plasma thermal deformation" to prepare the titanium alloy material. The operation is simple, and a fine microstructure and a fully dense titanium alloy material can be obtained, which significantly improves the strength and toughness of the titanium alloy material.

[0007] The purpose of the present invention is achieved through the following technical solutions.

[0008] A method for preparing a titanium alloy with an ultrafine grain structure, the method comprising the following steps:

[0009] (1) Mechanical ball milling:

[0010] The titanium alloy powder and the pure copper powder are added into a ball mill jar for ball milling and mixing, and then evaporated and dried to obtain a uniformly mixed powder.

[0011] The preferred titanium alloy powder is TC4 spherical powder; the preferred titanium alloy particle size is 15 to 53 μm;

[0012] The preferred copper powder particle size is 50 to 100 nm;

[0013] The mass fraction of the titanium alloy powder is 92-97 wt.%, and the mass fraction of the copper powder is 3-8 wt.%.

[0014] The preferred grinding balls are stainless steel grinding balls, with a mass ratio of large: medium: small balls of 2:3:5, a large ball diameter of 8 mm, a medium ball diameter of 5 mm, and a small ball diameter of 2 mm;

[0015] The preferred ball mill is an omnidirectional planetary ball mill; the preferred ball milling parameters are: ball-to-material mass ratio 4-10:1; ball mill speed 100-300 rpm / min; ball milling time 1-8h, each ball milling 1h, stop 10min; ball milling medium is ethanol.

[0016] (2) Spark plasma sintering:

[0017] The mixed powder obtained in step (1) is loaded into a graphite mold with an inner diameter of Φ1 and spark plasma sintering is performed in an SPS system.

[0018] The specific sintering parameters are: initial pressure of 1MPa, heating rate of 100℃ / min, sintering temperature of 800℃~900℃; axial pressure of 50MPa~70MPa; insulation and pressure holding time of 5~10min; after the insulation and pressure holding is completed, the current is cut off, the pressure is released, and the furnace is cooled to below 200℃, taken out, and polished until there is no graphite paper residue on the surface to obtain a titanium alloy material with an equiaxed organizational structure.

[0019] The preferred inner diameter of the graphite die is 20 mm.

[0020] (3) Quenching:

[0021] The titanium alloy material with an equiaxed structure obtained in step (2) is placed in a muffle furnace, heated to 950°C at a heating rate of 10°C / min, and kept at 950°C for 10 to 15 minutes. After the insulation is completed, the titanium alloy with an equiaxed structure is immediately quenched to obtain a titanium alloy material with a needle-like structure.

[0022] The preferred quenching liquid is distilled water.

[0023] (4) Discharge plasma thermal deformation:

[0024] The titanium alloy material with needle-like structure obtained in step (3) is placed in a carbon fiber mold with an inner diameter of Φ2 for discharge plasma thermal deformation.

[0025] The specific parameters are: the initial pressure is 1MPa, the temperature is increased to 760-800℃ at a heating rate of 50℃ / min, and then kept warm for 5-10min. After the insulation, pressure is applied for thermal deformation. When the deformation reaches 70-75%, the current is turned off, and the pressure is released when the temperature drops to 600℃. The furnace is cooled to below 200℃ and a titanium alloy material with ultrafine grain structure is obtained.

[0026] The preferred carbon fiber mold inner diameter is 40 mm.

[0027] The present invention has the beneficial effects:

[0028] (1) The present invention provides a method for preparing a titanium alloy material with an ultrafine grain structure, which adopts a technology combining ball milling-discharge plasma sintering-quenching-discharge plasma thermal deformation to obtain an ultrafine grain titanium alloy structure, thereby improving the strength of the titanium alloy material without sacrificing its plasticity.

[0029] (2) By introducing Cu into the titanium alloy material, due to the low solubility of Cu in α-Ti during hot deformation, Ti2Cu precipitation phase will be targeted at the interface between α-Ti and β-Ti during cooling, reducing the driving force of grain coarsening. At the same time, the in-situ precipitated Ti2Cu can effectively pin the interface between α-Ti and β-Ti. Therefore, an ultrafine-grained titanium alloy microstructure is obtained.

[0030] (3) This method is simple and easy to operate, highly practical, and has good industrial prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1a This is one of the microstructure photos of the titanium alloy material prepared in Example 2.

[0032] Figure 1b This is the second microstructure photograph of the titanium alloy material prepared in Example 2.

[0033] Figure 2 This is the engineering stress-engineering strain curve of the titanium alloy material prepared in Example 2. DETAILED DESCRIPTION

[0034] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments, but this is not intended to limit the present invention.

[0035] In the following comparative examples and embodiments:

[0036] The TC4 spherical powder is provided by Beijing Xingrongyuan Technology Co., Ltd., and its particle size range is 15 μm to 53 μm.

[0037] The Cu powder is provided by Hebei Zhongtian New Materials Co., Ltd., and its particle size ranges from 50nm to 100nm.

[0038] The relative density of the prepared titanium alloy material is measured and calculated according to the Archimedean principle.

[0039] The model of the SPS sintering system is Dr. Sinter: Model SPS-3.20MK-IV.

[0040] The tensile mechanical properties are all tested on a universal material testing machine (INSTRON 5985), and the size of the parallel section of the sample used for the tensile test is 8 mm×2 mm×2 mm.

[0041] The microstructure observation is performed using a field emission scanning electron microscope, and the model of the field emission scanning electron microscope is Hitachi S-4800N.

[0042] Example 1

[0043] (1) Mechanical ball milling:

[0044] 48.5 g of spherical TC4 powder and 1.5 g of copper powder were placed in a 500 ml stainless steel ball mill, and 500 g of stainless steel grinding balls were added according to a ball-to-material ratio of 10:1, and anhydrous ethanol was added as a protective liquid. The mixture was ball-milled at a speed of 300 rpm / min on an omnidirectional planetary ball mill for 1 h. The ball-milled powder was then poured into a rotary evaporator for drying to obtain a 3 wt.% Cu+TC4 mixed powder.

[0045] (2) SPS sintering: 15 g of 3 wt.% Cu+TC4 mixed powder was placed in a graphite mold with an inner diameter of 20 mm and sintered in an SPS system.

[0046] The specific sintering parameters are as follows: the initial pressure is 1MPa, the temperature is increased at a heating rate of 100℃ / min, and the pressure is applied when the temperature rises to 700℃. After the sintering temperature reaches 800℃, the temperature is kept at this temperature for 10min. At this time, the axial pressure is 50MPa. After the heat preservation and pressure holding is completed, the current is cut off, the pressure is released, and the material is cooled to below 200℃ in the furnace, taken out, and demolded to obtain a titanium alloy material with an equiaxed structure.

[0047] (3) Quenching: The titanium alloy material with an equiaxed structure was polished with sandpaper until no graphite paper remained on the surface. The material was then placed in a muffle furnace and heated to 950°C at a heating rate of 10°C / min and kept at 950°C for 10 min. After the insulation, the sample was immediately water quenched to obtain a titanium alloy material with a needle-like structure.

[0048] (4) SPS thermal deformation:

[0049] The titanium alloy material with needle-like structure is loaded into a carbon fiber mold with an inner diameter of 40 μm for discharge plasma thermal deformation.

[0050] The specific deformation parameters are: the initial pressure is 1MPa, the temperature is increased to 760℃ at a heating rate of 50℃ / min and kept at this temperature for 10 minutes, pressure is applied after the insulation is completed, and when the deformation reaches 70%, the current is turned off and the temperature begins to drop. When the temperature drops to 600℃, the pressure is released, and the furnace is cooled to below 200℃ to obtain the titanium alloy material with ultrafine grain structure.

[0051] The obtained titanium alloy material was subjected to relevant performance tests, and the results were as follows:

[0052] (1) The titanium alloy material obtained in Example 1 was subjected to a density test, and the density of the titanium alloy was measured to be 99.4%.

[0053] (2) The structure of the titanium alloy material obtained in Example 1 was observed. No holes were observed on the surface, and the structure was fine, dense and uniform, consisting of α-Ti, β-Ti and Ti2Cu in phase.

[0054] (3) The tensile mechanical properties of the titanium alloy material obtained in Example 1 were tested using a universal material testing machine. The tensile strength was 1196 MPa and the elongation was 8.5%.

[0055] Example 2

[0056] (1) Mechanical ball milling:

[0057] 47.5 g of spherical TC4 powder and 2.5 g of copper powder were placed in a 500 ml stainless steel ball mill, and 500 g of stainless steel grinding balls were added according to a ball-to-material ratio of 4:1, and anhydrous ethanol was added as a protective liquid. The ball mill was carried out on an omnidirectional planetary ball mill at a speed of 200 rpm / min for 8 h. The milling was stopped for 10 min after each hour of ball milling. The ball-milled powder was then poured into a rotary evaporator for drying to obtain a 5 wt.% Cu+TC4 mixed powder.

[0058] (2) SPS sintering: 15 g of 5 wt.% Cu+TC4 mixed powder was placed in a graphite mold with an inner diameter of 20 mm and sintered in an SPS system.

[0059] The specific sintering parameters are as follows: the initial pressure is 1MPa, the temperature is increased at a heating rate of 100℃ / min, and the pressure is applied when the temperature rises to 800℃. After the sintering temperature reaches 900℃, the temperature is kept at this temperature for 5min. At this time, the axial pressure is 70MPa. After the heat preservation and pressure holding is completed, the current is cut off, the pressure is released, and the material is cooled to below 200℃ in the furnace, taken out, and demolded to obtain a titanium alloy material with an equiaxed structure.

[0060] (3) Quenching: The obtained titanium alloy material with equiaxed structure was polished with sandpaper until no graphite paper remained on the surface, and then placed in a muffle furnace and heated to 950°C at a heating rate of 10°C / min, and kept at 950°C for 15 min. After the insulation, the sample was immediately water quenched to obtain a titanium alloy material with a needle-like structure.

[0061] (4) SPS thermal deformation:

[0062] The titanium alloy material with needle-like structure is loaded into a carbon fiber mold with an inner diameter of 40 μm for discharge plasma thermal deformation.

[0063] The specific deformation parameters are: the initial pressure is 1MPa, the temperature is increased to 780℃ at a heating rate of 50℃ / min and kept at this temperature for 5min, pressure is applied after the insulation is completed, and when the deformation reaches 75%, the current is turned off and the temperature begins to drop. When the temperature drops to 600℃, the pressure is released, and the furnace is cooled to below 200℃ to obtain the titanium alloy material with ultrafine grain structure.

[0064] The obtained titanium alloy material was subjected to relevant performance tests, and the results were as follows:

[0065] (1) The titanium alloy material obtained in Example 2 was subjected to a density test, and the density of the titanium alloy was measured to be 99.5%.

[0066] (2) The microstructure of the titanium alloy material obtained in Example 2 was observed. No holes were observed on the surface, the microstructure was dense and uniform, and the microstructure was composed of fine α-Ti, β-Ti and interlaced Ti2Cu. Figure 1a and Figure 1b This is a scanning electron microscope image of Example 2.

[0067] (3) The tensile mechanical properties of the titanium alloy material prepared in Example 2 were tested using a universal material testing machine. The tensile strength was 1178 MPa and the elongation was 10.0%. Figure 2 This is the engineering stress-engineering strain curve of Example 2.

[0068] Example 3

[0069] (1) Mechanical ball milling:

[0070] 46 g of spherical TC4 powder and 4 g of copper powder were charged into a 500 ml stainless steel ball mill, and 500 g of stainless steel grinding balls were added according to a ball-to-material ratio of 8:1, and anhydrous ethanol was added as a protective liquid. The ball mill was carried out on an omnidirectional planetary ball mill at a speed of 100 rpm / min for 6 h. The milling was stopped for 10 min after each hour of ball milling. The ball-milled powder was then poured into a rotary evaporator for drying to obtain an 8 wt.% Cu+TC4 mixed powder.

[0071] (2) SPS sintering: 15 g of 8 wt.% Cu+TC4 mixed powder was placed in a graphite mold with an inner diameter of 20 mm and sintered in an SPS system.

[0072] The specific sintering parameters are as follows: the initial pressure is 1MPa, the temperature is increased at a heating rate of 100℃ / min, and the pressure is applied when the temperature rises to 750℃. After the sintering temperature reaches 850℃, the temperature is kept at this temperature for 8min. At this time, the axial pressure is 60MPa. After the heat preservation and pressure holding is completed, the current is cut off, the pressure is released, and the material is cooled to below 200℃ in the furnace, taken out, and demolded to obtain a titanium alloy material with an equiaxed structure.

[0073] (3) Quenching: The obtained titanium alloy material with equiaxed structure was polished with sandpaper until no graphite paper remained on the surface, and then placed in a muffle furnace and heated to 950°C at a heating rate of 10°C / min, and kept at 950°C for 12 min. After the insulation, the sample was immediately water quenched to obtain a titanium alloy material with a needle-like structure.

[0074] (4) SPS thermal deformation:

[0075] The titanium alloy material with needle-like structure is loaded into a carbon fiber mold with an inner diameter of 40 μm for discharge plasma thermal deformation.

[0076] The specific deformation parameters are: the initial pressure is 1 MPa, the temperature is increased to 800°C at a heating rate of 50°C / min and kept at this temperature for 8 minutes, pressure is applied after the insulation is completed, and when the deformation reaches 70%, the current is turned off and the temperature begins to drop. When the temperature drops to 600°C, the pressure is released, and the furnace is cooled to below 200°C and taken out to obtain the titanium alloy material with ultrafine grain structure.

[0077] The obtained titanium alloy material was subjected to relevant performance tests, and the results were as follows:

[0078] (1) The titanium alloy material obtained in Example 3 was subjected to a density test, and the density of the titanium alloy was measured to be 99.5%.

[0079] (2) The microstructure of the titanium alloy material obtained in Example 3 was observed. No holes were observed on the surface, the microstructure was dense and uniform, and the microstructure was composed of fine α-Ti, β-Ti and interlaced Ti2Cu.

[0080] (3) The tensile mechanical properties of the titanium alloy material obtained in Example 2 were tested using a universal material testing machine. The tensile strength was 1171 MPa and the elongation was 7.4%.

[0081] The present invention includes but is not limited to the above embodiments. Any equivalent replacement or partial improvement made under the principle of the spirit of the present invention shall be deemed to be within the protection scope of the present invention.

Claims

1. A method for preparing a titanium alloy having an ultrafine grain structure, characterized in that: The method steps are as follows: (1) Mechanical ball milling: titanium alloy powder and pure copper powder are added into a ball mill for mixing, and then evaporated and dried to obtain a uniformly mixed powder; Ball milling parameters are: ball-to-material mass ratio 4-10:1; ball mill speed 100-300 rpm / min; ball milling time 1-8 hours, 1 hour of ball milling and 10 minutes of downtime; ball milling medium is ethanol; The grinding balls are made of stainless steel, with a mass ratio of large, medium and small balls of 2:3:5, with a large ball diameter of 8mm, a medium ball diameter of 5mm and a small ball diameter of 2mm. (2) Spark plasma sintering: the mixed powder obtained in step (1) is loaded into a graphite mold and spark plasma sintered in an SPS system; The sintering parameters in step (2) are as follows: initial pressure of 1 MPa, heating rate of 100°C / min, sintering temperature of 800°C-900°C; axial pressure of 50 MPa-70 MPa; heat preservation and pressure holding time of 5-10 min; after the heat preservation and pressure holding is completed, the current is cut off, the pressure is released, the furnace is cooled to below 200°C, taken out, and polished until no graphite paper remains on the surface, thereby obtaining a titanium alloy material with an equiaxed structure; In step (2), the inner diameter of the mold is 20 mm; (3) Quenching: quenching the titanium alloy material with an equiaxed structure obtained in step (2); The titanium alloy material with an equiaxed structure is placed in a muffle furnace, heated to 950°C at a heating rate of 10°C / min, and kept at 950°C for 10-15 minutes. After the holding period, the titanium alloy with an equiaxed structure is immediately quenched to obtain a titanium alloy material with a needle-like structure. (4) Discharge plasma thermal deformation: the titanium alloy material with needle-like structure obtained in step (3) is placed in a carbon fiber mold for discharge plasma thermal deformation; the inner diameter of the mold in step (4) is 40 mm; In step (4), the initial pressure is 1 MPa, the temperature is raised to 760-800°C at a heating rate of 50°C / min, and then the temperature is kept at this temperature for 5-10 minutes. After the end of the heat preservation, pressure is applied to perform thermal deformation. When the deformation reaches 70-75%, the current is turned off, and the pressure is released when the temperature drops to 600°C. The furnace is cooled to below 200°C and then taken out to obtain a titanium alloy material with an ultrafine grain structure. By introducing Cu into the titanium alloy material, the solubility of Cu in α-Ti is low during hot deformation, and the targeted precipitation of Ti2Cu precipitate phase at the interface of α-Ti and β-Ti during cooling reduces the driving force of grain coarsening; at the same time, the in-situ precipitated Ti2Cu effectively pins the interface of α-Ti and β-Ti.

2. The method for preparing a titanium alloy having an ultrafine grain structure according to claim 1, characterized in that: In step (1), the titanium alloy powder is TC4 powder with a particle size of 15-53 μm; and the copper powder has a particle size of 50-100 nm.

3. The method for preparing a titanium alloy having an ultrafine grain structure according to claim 1, characterized in that: The quenching liquid in step (3) is distilled water.

4. The method for preparing a titanium alloy having an ultrafine grain structure according to claim 1, characterized in that: In step (1): the mass fraction of the titanium alloy powder is 92-97 wt.%, and the mass fraction of the copper powder is 3-8 wt.%.

5. A titanium alloy with an ultrafine grain structure, obtained according to the preparation method according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • High-ductility titanium based ultra-fine crystal composite material and method for producing the same

    CN101492781A